Understanding insurance from islamic perspective (2017)
Without insurance, the business world may not be sustainable since all businesses have their inherent risks and therefore, may not have capacity to accommodate them particularly in this ever changing global economy. Managing the risks then becomes imperative. It is against this backdrop that this paper examines how insurance and takaful (Islamic Insurance) can protect the public, insurance policy holders and consumers; and thus build a strong national takaful industry to foster economic development. From the historical perspective, the paper reviews the operation of insurance right from the pre- Islamic period. The main purpose of this paper is to address the compatibility and non-compatibility of insurance in relation to Islam through a comparison of insurance and takaful. By comparing the two, it is possible to evaluate the benefits of takaful over conventional insurance. From the theoretical analysis employed, we found that the concept of insurance does not contradict the dictates of Islam. However, some of the means and methods that are currently being used in the conventional insurance are not Shari'ah compliant. From the analysis of theoretical aspect, a Shari'ah compliant Takaful must be devoid of riba (interest), gharar (uncertainty) and cooperation in sins. The paper also shows that despite the long history of insurance, the attempt to introduce takaful in Nigeria has not gained enough ground for only a few conventional insurance companies such as African Alliance Insurance, Niger Insurance Plc and Cornerstone Insurance Plc have added takaful to their operations. No full-fledged takaful company is in existence. With Guidelines 2013, issued by the National Insurance Commision, many insurance companies should be established to serve as backbones for emerging the Islamic finance in Nigeria.